CD271 defines a stem cell-like population in hypopharyngeal cancer. - Takayuki Imai (Public Library of Science (PLoS), 2013)
Cancer stem cells contribute to the malignant phenotypes of a variety of cancers, but markers to identify human hypopharyngeal cancer (HPC) stem cells remain poorly understood. Here, we report that the CD271(+) population sorted from xenotransplanted HPCs possesses an enhanced tumor-initiating capability in immunodeficient mice. Tumors generated from the CD271(+) cells contained both CD271(+) and CD271(-) cells, indicating that the population could undergo differentiation. Immunohistological analyses of the tumors revealed that the CD271(+) cells localized to a perivascular niche near CD34(+) vasculature, to invasive fronts, and to the basal layer. In accordance with these characteristics, a stemness marker, Nanog, and matrix metalloproteinases (MMPs), which are implicated in cancer invasion, were significantly up-regulated in the CD271(+) compared to the CD271 (-) cell population. Furthermore, using primary HPC specimens, we demonstrated that high CD271 expression was correlated with a poor prognosis for patients. Taken together, our findings indicate that CD271 is a novel marker for HPC stem-like cells and for HPC prognosis.